2009
DOI: 10.2172/983010
|View full text |Cite
|
Sign up to set email alerts
|

Kinase Expression and Chromosomal Rearrangements in Papillary Thyroid Cancer Tissues: Investigations at the Molecular and Microscopic Levels

Abstract: Structural chromosome aberrations are known hallmarks of many solid tumors. In the papillary form of thyroid cancer (PTC), for example, activation of the receptor tyrosine kinase (RTK) genes, ret or the neurotrophic tyrosine kinase receptor type I (NTRK1) by intra-or interchromosomal rearrangements have been suggested as a cause of the disease. The 1986 accident at the nuclear power plant in Chernobyl, Ukraine, led to the uncontrolled release of high levels of radioisotopes. Ten years later, the incidence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…However, single cell “visualization” techniques together with in silico approaches have been performed for identification of consequences of chromosome and genome instability (CIN and GIN, respectively) in the ataxia-telangiectasia (AT) brain [34]. Combining different “visualization” techniques is much more frequently applied and is usually referred to consequent application of molecular cytogenetic and immunocytochemistry methods [16, 31, 34-36]. Considering technological aspects of analyzing brain cells, an immuno-FISH protocol can provide for studying chromosome number/structure variations in neurons [16, 31, 34].…”
Section: Technological Principles For Single Cell Genomics Of the Brainmentioning
confidence: 99%
“…However, single cell “visualization” techniques together with in silico approaches have been performed for identification of consequences of chromosome and genome instability (CIN and GIN, respectively) in the ataxia-telangiectasia (AT) brain [34]. Combining different “visualization” techniques is much more frequently applied and is usually referred to consequent application of molecular cytogenetic and immunocytochemistry methods [16, 31, 34-36]. Considering technological aspects of analyzing brain cells, an immuno-FISH protocol can provide for studying chromosome number/structure variations in neurons [16, 31, 34].…”
Section: Technological Principles For Single Cell Genomics Of the Brainmentioning
confidence: 99%
“…In gene expression studies reported elsewhere, we were able to demonstrate that cell line S48T expresses the tyrosine kinase domain of NTRK-1 [44], which is normally located on the long arm of chromosome 1, band q12–21 [1] at position 156,830,671–156,851,642 bp in the UC Santa Cruz (UCSC) genome browser. For the analysis of chromosome 1 rearrangements, we pooled three individual BAC probes, since this has resulted in more reliable FISH signals [45,54,55].…”
Section: Resultsmentioning
confidence: 99%
“…It widely occurs in papillary and follicular types and its incidence has been increasing (Amrosini et al, 2011;Mondal et al, 2011;Sedov and Khmelevskaia, 2011;Caglar et al, 2012;Quan et al, 2012;Lerch and Richter, 2012). Early and/or late stage types of DTC may initiate by point mutations in different proto-oncogenes such as; RET, B-RAF, NTRK1 and K-RAS (Moura et al, 2011;Namba et al, 2003), functional gene inactivation that is triggered by point mutations (Weier et al, 2009;Moses et al, 2010) and epigenetic alterations in some target genes (Sharma et al, 2010;Lu et al, 2011). Despite remarkable advances have occurred in recent years in understanding the etyopatogenesis of thyroid cancer, the exact molecular etiological mechanism still remain unclear.…”
Section: Introductionmentioning
confidence: 99%